Hyperbaric oxygen therapy for delayed radiation injuries in gynecological cancers. Issue 2 (1st March 2006) - Fink, D.; Chetty, N.; Lehm, J. P.; Marsden, D. E.; Hacker, N. F.
Abstract : Delayed radiation-induced injuries are difficult to treat. The treatment of delayed radiation injuries with hyperbaric oxygen therapy (HBOT) is reported in small case series and case reports. This study reports the experience of a single institution with HBOT in delayed radiation injuries in patients with gynecological cancers. At least 20 sessions of 100% oxygen inhalation at 2.4 Atmospheric Absolutes (ATA) for 90 min in a hyperbaric chamber were carried out. Of the 14 patients included in the study, 10 patients have healed or showed improvement of more than 50%, resulting in a success rate of 71%. Mean follow-up was 31.6 months (range 6–70 months). The adverse events were acceptable. HBOT should be considered for patients with delayed radiation injuries, not responding to other treatments.